Singlet oxygen, UV-A, and ozone - Packer, Lester; Sies, H. (Helmut), 1942- (Methods in enzymology, 2000)
Recent advances in understanding the biological role of singlet oxygen in the pathways of cellular responses to ultraviolet-A radiation: its key position in photodynamical effects, and its generation by photochemical (dark) reactions, e.g. by cells of the immune system such as eosinophils and macrophages, are the focus of this volume. The new methods and techniques responsible for the rapid progress in this area are presented. The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry.